Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan di SDS Islam Terpadu Sulthoniyah Sambas - Mimi Mariana; Purniadi Putra; Jaelani (Jurnal Pendidikan Dasar Islam, 2023)
Educational institutions require planned handling by utilizing educational resources so that the results achieved are optimal, effective and efficient. Optimizing the use of educational resources requires a good leadership role, therefore the results of research on the role of the principal's leadership in improving the quality of education at the Sulthoniyah Sambas Integrated Islamic School are that the role of the principal is: The role of the principal as an educator, namely that the principal consistently guides teachers by carrying out workshops, education staff, students, developing all staff and providing good examples in the learning process.